A review of hedgehog signaling in cranial bone development - Pan, Angel; Chang, Le; Nguyen, Alan; James, Aaron W. (Frontiers in Physiology, 2013)
During craniofacial development, the Hedgehog (HH) signaling pathway is essential for mesodermal tissue patterning and differentiation. The Hedgehog family consists of three protein ligands: Sonic Hedgehog (SHH), Indian Hedgehog (IHH), and Desert Hedgehog (DHH), of which two are expressed in the craniofacial complex (IHH and SHH). Dysregulations in HH signaling are well documented to result in a wide range of craniofacial abnormalities, including holoprosencephaly, hypotelorism, and cleft lip/palate. Furthermore, mutations in HH effectors, co-receptors, and ciliary proteins result in skeletal and craniofacial deformities. Cranial suture morphogenesis is a delicate developmental process that requires control of cell commitment, proliferation and differentiation. This review focuses on both what is known and what remains unknown regarding HH signaling in cranial suture morphogenesis and intramembranous ossification. As demonstrated from murine studies, expression of both SHH and IHH is critical to the formation and fusion of the cranial sutures and calvarial ossification. SHH expression has been observed in the cranial suture mesenchyme and its precise function is not fully defined, although some postulate SHH to delay cranial suture fusion. IHH expression is mainly found on the osteogenic fronts of the calvarial bones, and functions to induce cell proliferation and differentiation. Unfortunately, neonatal lethality of deficient mice precludes a detailed examination of their postnatal calvarial phenotype. In summary, a number of basic questions are yet to be answered regarding domains of expression, developmental role, and functional overlap of HH morphogens in the calvaria. Nevertheless, SHH and IHH ligands are integral to cranial suture development and regulation of calvarial ossification. When HH signaling goes awry, the resultant suite of morphologic abnormalities highlights the important roles of HH signaling in cranial development.